Impact of Supplier Management Strategies on the Organizational Performance of ISO 9001 Certified Organizations - Fonseca, Luís Miguel (2015)
Purpose: The purpose of this article is to discuss the impact of Supplier orientation and the resulting Supply Chain Management (SCM) approach, on the organizational performance of ISO 9001 Quality Management Systems certified organizations. Methodology/Approach: Following a literature review, a full structural conceptual model was proposed. An online survey was administered to managers of Portuguese organizations with certified ISO 9001 Quality Management Systems. Descriptive Statistics and Structural Model Equations were used to validate the proposed conceptual model. Findings: There are positive relationships between Organization Strategy and Supplier Orientation, between Supplier Orientation and Stakeholders Satisfaction, and between Stakeholders Satisfaction and Organizational Performance Orientation, supporting ISO 9001:2015. These findings provide insights that supplier orientation, mediated by stakeholder satisfaction, is an essential tool for organizational competitive sustainable advantage. Research Limitation/implication: The analysis was based on managers of ISO 9001 certified organizations perceptions, so additional studies with actual data and longitudinal studies should be useful for further validation. Originality/Value of paper: The importance of the overall organizational ecosystem is highlighted with potential impact on the more than 1 Million ISO 9001 organizations certified worldwide and in their suppliers.